KULTUR JARINGAN RUMPUT LAUT KAPPAPHYCUS ALVAREZII DENGAN METODE EMBRIOGENESIS SOMATIK - BETARI ATHIYAH IRAWATI; RANGGA IDRIS AFFANDI (GANEC SWARA, 2024)
Seaweed is a leading aquaculture commodity with the largest production among other leading commodities. One of the seaweed that is widely cultivated in Indonesia is Kappaphycus alvarezii. Kappaphycus alvarezii is one of the main aquaculture commodities which is widely cultivated because its production technology is relatively cheap and easy, and post-harvest handling is relatively simple. One of the problems in seaweed cultivation is the use of poor quality seaweed seeds. One of the efforts to increase seaweed production is to use quality seeds, namely tissue culture. The aim of this research is to determine work steps, identify problems and identify the level of success of tissue culture activities on Kappaphycus alvarezii seaweed so that maximum production results can then be achieved. This research was carried out in March-May 2023 at the Center for Brackish Water Aquaculture Fisheries (BBPBAP) Jepara, Central Java. The results obtained were Kappaphycus alvarezii tissue culture activities including sea water preparation, sterilization of tools and materials, making paste fertilizer, media preparation, selection and acclimatization of broodstock, sterilization and cutting of explants, planting explants, callus induction, regeneration of callus into micropropagules, regeneration of micropropagules into plantlets, and water quality management needs to be carried out to support the success of seaweed tissue culture